# Conditions for the validity of a class of optimal Hilbert type multiple integral inequalities with nonhomogeneous kernels

## Abstract

For the Hilbert type multiple integral inequality

$$\int _{\mathbb{R}_{+}^{n}} \int _{\mathbb{R}_{+}^{m}} K\bigl( \Vert x \Vert _{m,\rho }, \Vert y \Vert _{n, \rho }\bigr) f(x)g(y) \,\mathrm{d} x \,\mathrm{d} y \leq M \Vert f \Vert _{p, \alpha } \Vert g \Vert _{q, \beta }$$

with a nonhomogeneous kernel $$K(\|x\|_{m, \rho }, \|y\|_{n, \rho })=G(\|x\|^{\lambda _{1}}_{m, \rho }/ \|y\|^{\lambda _{2}}_{n, \rho })$$ ($$\lambda _{1}\lambda _{2}> 0$$), in this paper, by using the weight function method, necessary and sufficient conditions that parameters p, q, $$\lambda _{1}$$, $$\lambda _{2}$$, α, β, m, and n should satisfy to make the inequality hold for some constant M are established, and the expression formula of the best constant factor is also obtained. Finally, their applications in operator boundedness and operator norm are also considered, and the norms of several integral operators are discussed.

## 1 Introduction and preparatory knowledge

Let $$k \in \mathbb{N}=\{1, 2, 3, \ldots \}$$, $$\rho >0$$, $$x=(x_{1}, x_{2}, \ldots , x_{k})$$, $$\mathbb{R}_{+}^{k}=\{x= (x_{1}, x_{2}, \ldots , x_{k} ) : x_{i}>0, i=1,2, \ldots , k\}$$, $$\|x\|_{k,\rho }= (x_{1}^{\rho }+x_{2}^{\rho }+\cdots +x_{k}^{\rho } )^{1 / \rho }$$. Define

$$L_{p}^{\alpha } \bigl(\mathbb{R}_{+}^{k} \bigr)= \biggl\{ f(x) \geq 0 : \Vert f \Vert _{p, \alpha }= \biggl( \int _{\mathbb{R}_{+}^{k}} \Vert x \Vert ^{\alpha }_{k, \rho } f^{p}(x) \,\mathrm{d} x \biggr)^{1 / p}< +\infty \biggr\} .$$

In this paper, for a class of nonhomogeneous kernels $$K(\|x\|_{m, \rho }, \|y\|_{n, \rho })=G(\|x\|^{\lambda _{1}}_{m, \rho }/ \|y\|^{\lambda _{2}}_{n, \rho })$$ ($$\lambda _{1}\lambda _{2}>0$$), we discuss the equivalent parameter conditions for the validity of Hilbert type multiple integral inequality

$$\int _{\mathbb{R}_{+}^{n}} \int _{\mathbb{R}_{+}^{m}} K\bigl( \Vert x \Vert _{m, \rho }, \Vert y \Vert _{n, \rho }\bigr) f(x)g(y) \,\mathrm{d} x \,\mathrm{d} y \leq M \Vert f \Vert _{p, \alpha } \Vert g \Vert _{q, \beta }.$$
(1)

That is, what conditions do parameters $$\lambda _{1}$$, $$\lambda _{2}$$, p, q, α, β satisfy to make (1) hold? On the contrary, what conditions do the parameters satisfy when (1) holds? Meanwhile, the best constant factor and its application in operator theory are also considered.

In , we studied the necessary and sufficient conditions for the validity of Hilbert type multiple integral inequalities with kernel $$K(\|x\|_{m, \rho }, \|y\|_{n, \rho })=G(\|x\|^{\lambda _{1}}_{m, \rho } \|y\|^{\lambda _{2}}_{n, \rho })$$ ($$\lambda _{1}\lambda _{2}>0$$). The present paper is a supplement and improvement of , more relevant research can be referred to .

### Lemma 1.1

()

Let $$p_{i}>0$$, $$a_{i}>0$$, $$\alpha _{i}>0(i=1,2, \ldots , n), \psi (u)$$ be measurable. Then

\begin{aligned}& \int _{ (\frac{x_{1}}{a_{1}} )^{\alpha _{1}}+\cdots + (\frac{x_{n}}{a_{n}} )^{\alpha _{n}} \leq 1; x_{i}>0} { \psi } \biggl( \biggl(\frac{x_{1}}{a_{1}} \biggr)^{\alpha _{1}}+\cdots + \biggl(\frac{x_{n}}{a_{n}} \biggr)^{\alpha _{n}} \biggr) x_{1}^{p_{1}-1} \cdots x_{n}^{p_{n}-1} \,\mathrm{d} x_{1} \cdots \, \mathrm{d} x_{n} \\& \quad = \frac{a_{1}^{p_{1}} \cdots a_{n}^{p_{n}} \Gamma (\frac{p_{1}}{\alpha _{1}} ) \cdots \Gamma (\frac{p_{n}}{\alpha _{n}} )}{\alpha _{1} \cdots \alpha _{n} \Gamma (\frac{p_{1}}{\alpha _{1}}+\cdots +\frac{p_{n}}{\alpha _{n}} )} \int _{0}^{1} \psi (u) u^{\frac{p_{1}}{\alpha _{1}}+\cdots + \frac{p_{n}}{\alpha _{n}}-1} \, \mathrm{d} u, \end{aligned}

where $$\Gamma (t)$$ represents the gamma function.

By using Lemma 1.1, under the same conditions, it is not difficult to obtain: Let $$\varphi (u)$$ be measurable, $$\rho >0$$, $$n\geq 1$$, $$x=(x_{1}, x_{2}, \ldots , x_{n}) \in \mathbb{R}_{+}^{n}$$. Then

\begin{aligned}& \begin{gathered} \int _{ \Vert x \Vert _{n,\rho } \leq r} \varphi \bigl( \Vert x \Vert _{n,\rho } \bigr) \,\mathrm{d} x= \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \int _{0}^{r} \varphi (u) u^{n-1} \,\mathrm{d} u, \\ \int _{ \Vert x \Vert _{n,\rho } \geq r} \varphi \bigl( \Vert x \Vert _{n,\rho } \bigr) \,\mathrm{d} x= \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \int _{r}^{+ \infty } \varphi (u) u^{n-1} \, \mathrm{d} u. \end{gathered} \end{aligned}
(2)

Suppose that $$K(u, v)=G(u^{\lambda _{1}}/{v^{\lambda _{2}}})$$, then obviously $$K(u, v)$$ satisfies the following property:

$$K(u, v)=K\bigl(1,u^{{-\lambda _{1}}/{\lambda _{2}}}v\bigr)=K\bigl(v^{{-\lambda _{2}}/{ \lambda _{1}}}u, 1\bigr).$$

### Lemma 1.2

Let $$\frac{1}{p}+\frac{1}{q}=1(p>1)$$, $$\rho >0$$, $$m,n\in \mathbb{N}$$, $$K(\|x\|_{m, \rho }, \|y\|_{n, \rho })=G(\|x\|^{\lambda _{1}}_{m, \rho }/\|y\|^{ \lambda _{2}}_{n, \rho })$$, $$\alpha , \beta \in \mathbb{R}$$. Then

\begin{aligned} \omega _{1}(m, \alpha , p, y) =& \int _{\mathbb{R}_{+}^{m}} K\bigl( \Vert x \Vert _{m, \rho }, \Vert y \Vert _{n, \rho }\bigr) \Vert x \Vert ^{-\frac{\alpha +m}{p}}_{m, \rho } \,\mathrm{d} x \\ =& \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \Vert y \Vert _{n,\rho }^{\frac{\lambda _{2}}{\lambda _{1}} (- \frac{\alpha +m}{p}+m )} \int _{0}^{+\infty } K(t, 1) t^{- \frac{\alpha +m}{p}+m-1} \, \mathrm{d} t \\ :=& \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \Vert y \Vert _{n,\rho }^{\frac{\lambda _{2}}{\lambda _{1}} (- \frac{\alpha +m}{p}+m )}W_{1}, \end{aligned}
(3)
\begin{aligned} \omega _{2}(n, \beta , q, x) =& \int _{\mathbb{R}_{+}^{n}} K\bigl( \Vert x \Vert _{m, \rho }, \Vert y \Vert _{n, \rho }\bigr) { \Vert y \Vert _{n, \rho }}^{-\frac{\beta +n}{q}} \,\mathrm{d} y \\ =& \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \Vert x \Vert _{m,\rho }^{\frac{\lambda _{1}}{\lambda _{2}} (- \frac{\beta +n}{q}+n )} \int _{0}^{+\infty } K(1, t) t^{- \frac{\beta +n}{q}+n-1} \, \mathrm{d} t \\ :=& \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \Vert x \Vert _{m,\rho }^{\frac{\lambda _{1}}{\lambda _{2}} (- \frac{\beta +n}{q}+n )}W_{2}. \end{aligned}
(4)

Moreover, if $$\frac{n\lambda _{1}-\alpha \lambda _{2}}{p}+ \frac{m\lambda _{2}-\beta \lambda _{1}}{q}=0$$, then $$\lambda _{1}W_{1}=\lambda _{2}W_{2}$$.

### Proof

It follows from (2) that

\begin{aligned} \omega _{1}(m, \alpha , p, y) =& \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \int _{0}^{+ \infty } K\bigl(u, \Vert y \Vert _{n,\rho }\bigr) u^{-\frac{\alpha +m}{p}+m-1} \,\mathrm{d} u \\ =& \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \int _{0}^{+\infty } K\bigl( \Vert y \Vert _{n,\rho }^{-{\lambda _{2}}/{\lambda _{1}}}u, 1\bigr) u^{-\frac{\alpha +m}{p}+m-1} \,\mathrm{d} u \\ =& \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \Vert y \Vert _{n,\rho }^{\frac{\lambda _{2}}{\lambda _{1}} (- \frac{\alpha +m}{p}+m-1 )+\frac{\lambda _{2}}{\lambda _{1}}} \\ &{}\times \int _{0}^{+\infty } K(t, 1) t^{-\frac{\alpha +m}{p}+m-1} \, \mathrm{d} t \\ =& \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \Vert y \Vert _{n,\rho }^{\frac{\lambda _{2}}{\lambda _{1}} (- \frac{\alpha +m}{p}+m )}W_{1}. \end{aligned}

(4) can be proved at the same time.

When $$\frac{n\lambda _{1}-\alpha \lambda _{2}}{p}+ \frac{m\lambda _{2}-\beta \lambda _{1}}{q}=0$$, notice that $$\lambda _{1}\lambda _{2}>0$$, we have

\begin{aligned} W_{1} =& \int _{0}^{+\infty } K(t, 1) t^{-\frac{\alpha +m}{p}+m-1} \, \mathrm{d} t \\ =& \int _{0}^{+\infty } K\bigl(1, t^{-\lambda _{1}/\lambda _{2}} \bigr) t^{- \frac{\alpha +m}{p}+m-1} \,\mathrm{d} t \\ =& \frac{\lambda _{2}}{\lambda _{1}} \int _{0}^{+\infty } K(1, u) u^{- \frac{\lambda _{2}}{\lambda _{1}}{ (-\frac{\alpha +m}{p}+m-1 )}-\frac{\lambda _{2}}{\lambda _{1}}-1} \, \mathrm{d} u \\ =& \frac{\lambda _{2}}{\lambda _{1}} \int _{0}^{+\infty } K(1, u) u^{{- \frac{\beta +n}{q}+n-1}} \, \mathrm{d} u \\ =& \frac{\lambda _{2}}{\lambda _{1}}W_{2}. \end{aligned}

Thus $$\lambda _{1}W_{1}=\lambda _{2}W_{2}$$. □

## 2 Main results

### Theorem 2.1

Let $$\frac{1}{p}+\frac{1}{q}=1(p>1)$$, $$\rho >0$$, $$m,n\in \mathbb{N}$$, $$\lambda _{1} \lambda _{2}>0$$, $$\alpha , \beta \in \mathbb{R}$$, $$K(\|x\|_{m, \rho }, \|y\|_{n, \rho })=G(\|x\|^{\lambda _{1}}_{m, \rho }/ \|y\|^{\lambda _{2}}_{n, \rho }) (\lambda _{1}\lambda _{2}>0)$$ be nonnegative measurable and

$$W_{0}= \vert \lambda _{1} \vert \int _{0}^{+\infty } K(t, 1) t^{- \frac{\alpha +m}{p}+m-1} \, \mathrm{d} t$$

be convergent. Then

(i) If and only if $$\frac{n\lambda _{1}-\alpha \lambda _{2}}{p}+ \frac{m\lambda _{2}-\beta \lambda _{1}}{q}=0$$, there exists a constant $$M>0$$ such that

$$\int _{\mathbb{R}_{+}^{n}} \int _{\mathbb{R}_{+}^{m}} K\bigl( \Vert x \Vert _{m, \rho }, \Vert y \Vert _{n, \rho }\bigr) f(x)g(y) \,\mathrm{d} x \,\mathrm{d} y \leq M \Vert f \Vert _{p, \alpha } \Vert g \Vert _{q, \beta },$$
(5)

where $$f(x) \in L_{p}^{\alpha }(\mathbb{R}_{+}^{m})$$, $$g(y) \in L_{q}^{\beta } (\mathbb{R}_{+}^{n} )$$.

(ii) When (5) holds, the best constant factor is

$$\inf M=\frac{W_{0}}{ \vert \lambda _{1} \vert ^{1/q} \vert \lambda _{2} \vert ^{1/p}} \biggl( \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \biggr)^{1 / q} \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \biggr)^{1 / p} .$$

### Proof

Let $$\frac{n\lambda _{1}-\alpha \lambda _{2}}{p}+ \frac{m\lambda _{2}-\beta \lambda _{1}}{q}=c$$.

(i) Suppose that (5) holds. We prove that $$c=0$$. Consider the case of $$\lambda _{1}>0$$, $$\lambda _{2}>0$$. If $$c>0$$, take $$0<\varepsilon <\frac{c}{\lambda _{1}\lambda _{2}}$$ and

\begin{aligned}& f(x)= \textstyle\begin{cases} { \Vert x \Vert _{m,\rho }^{(-\alpha -m-\lambda _{1}\varepsilon ) / p},} & { \Vert x \Vert _{m,\rho } \geq 1}, \\ {0,} & {0< \Vert x \Vert _{m,\rho }< 1},\end{cases}\displaystyle \\& g(y)= \textstyle\begin{cases} { \Vert y \Vert _{n,\rho }^{(-\beta -n-\lambda _{2}\varepsilon ) / q},} & { \Vert y \Vert _{n, \rho } \geq 1}, \\ {0,} & {0< \Vert y \Vert _{n, \rho }< 1}.\end{cases}\displaystyle \end{aligned}

Then

\begin{aligned}& \begin{aligned} M \Vert f \Vert _{p, \alpha } \Vert g \Vert _{q, \beta } ={}&M \biggl( \int _{ \Vert x \Vert _{m,\rho } \geq 1} \Vert x \Vert _{m,\rho }^{-m-\lambda _{1}\varepsilon } \,\mathrm{d} x \biggr)^{1 / p} \biggl( \int _{ \Vert y \Vert _{n,\rho } \geq 1} \Vert y \Vert _{n,\rho }^{-n- \lambda _{2}\varepsilon } \,\mathrm{d} y \biggr)^{1 / q} \\ ={}& M \biggl( \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \biggr)^{1 / p} \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \biggr)^{1 / q} \\ &{}\times \biggl( \int _{1}^{+\infty } u^{-1-\lambda _{1}\varepsilon } \,\mathrm{d} u \biggr)^{1 / p} \biggl( \int _{1}^{+\infty } u^{-1-\lambda _{2} \varepsilon } \,\mathrm{d} u \biggr)^{1 / q} \\ ={} & \frac{M}{\varepsilon \lambda ^{1/p}_{1}\lambda ^{1/q}_{2}} \biggl( \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \biggr)^{1 / p} \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \biggr)^{1 / q}, \end{aligned} \\& \int _{\mathbb{R}_{+}^{n}} \int _{\mathbb{R}_{+}^{m}} K\bigl( \Vert x \Vert _{m, \rho }, \Vert y \Vert _{n, \rho }\bigr) f(x)g(y) \,\mathrm{d} x \,\mathrm{d} y \\& \quad = \int _{ \Vert x \Vert _{m,\rho } \geq 1} \Vert x \Vert _{m,\rho }^{(-\alpha -m-\lambda _{1} \varepsilon ) / p} \biggl( \int _{ \Vert y \Vert _{m,\rho } \geq 1} K\bigl( \Vert x \Vert _{m, \rho }, \Vert y \Vert _{n, \rho }\bigr) \Vert y \Vert _{n,\rho }^{(-\beta -n-\lambda _{2} \varepsilon ) / q} \,\mathrm{d} y \biggr) \,\mathrm{d} x \\& \quad = \int _{ \Vert x \Vert _{m,\rho } \geq 1} \Vert x \Vert _{m,\rho }^{- \frac{\alpha +m+\lambda _{1}\varepsilon }{p}} \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \int _{1}^{+ \infty } K \bigl({ \Vert x \Vert _{m,\rho }}, u \bigr) {u}^{- \frac{\beta +n+\lambda _{2}\varepsilon }{q}+n-1} \,\mathrm{d} u \biggr) \, \mathrm{d} x \\& \quad = \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \int _{ \Vert x \Vert _{m,\rho } \geq 1} \Vert x \Vert _{m,\rho }^{- \frac{\alpha +m+\lambda _{1}\varepsilon }{p}} \biggl( \int _{1}^{+\infty } K \bigl({1, u \Vert x \Vert ^{-\lambda _{1}/\lambda _{2}}_{m,\rho }} \bigr) {u}^{- \frac{\beta +n+\lambda _{2}\varepsilon }{q}+n-1} \,\mathrm{d} u \biggr) \,\mathrm{d} x \\& \quad = \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \int _{ \Vert x \Vert _{m,\rho } \geq 1} \Vert x \Vert _{m,\rho }^{- \frac{\alpha +m+\lambda _{1}\varepsilon }{p}+ \frac{\lambda _{1}}{\lambda _{2}} (- \frac{\beta +n+\lambda _{2}\varepsilon }{q}+n-1 )+ \frac{\lambda _{1}}{\lambda _{2}}} \\& \qquad {}\times \biggl( \int _{ \Vert x \Vert ^{-\lambda _{1}/\lambda _{2}}_{m,\rho }}^{+ \infty } K(1, t) {t}^{- \frac{\beta +n+\lambda _{2}\varepsilon }{q}+n-1} \, \mathrm{d} t \biggr) \,\mathrm{d} x \\& \quad = \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \int _{ \Vert x \Vert _{m,\rho } \geq 1} \Vert x \Vert _{m,\rho }^{{-m+ \frac{c}{\lambda _{2}}-\lambda _{1}\varepsilon }} \biggl( \int _{ \Vert x \Vert ^{- \lambda _{1}/\lambda _{2}}_{m,\rho }}^{+\infty } K(1, t) {t}^{- \frac{\beta +n+\lambda _{2}\varepsilon }{q}+n-1} \, \mathrm{d} t \biggr) \,\mathrm{d} x \\& \quad \geq \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \int _{ \Vert x \Vert _{m,\rho } \geq 1} \Vert x \Vert _{m,\rho }^{{-m+ \frac{c}{\lambda _{2}}-\lambda _{1}\varepsilon }} \biggl( \int _{1}^{+ \infty } K(1, t) {t}^{- \frac{\beta +n+\lambda _{2}\varepsilon }{q}+n-1} \, \mathrm{d} t \biggr) \,\mathrm{d} x \\& \quad = \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \int _{1}^{+\infty } K(1, t) {t}^{- \frac{\beta +n+\lambda _{2}\varepsilon }{q}+n-1} \, \mathrm{d} t \int _{ \Vert x \Vert _{m,\rho } \geq 1} \Vert x \Vert _{m,\rho }^{{-m+\frac{c}{\lambda _{2}}- \lambda _{1}\varepsilon }} \,\mathrm{d} x \\& \quad = \frac{\Gamma ^{m+n}(1 / \rho )}{\rho ^{m+n-2} \Gamma (n / \rho )\Gamma (m / \rho )} \int _{1}^{+\infty } K(1, t) {t}^{- \frac{\beta +n+\lambda _{2}\varepsilon }{q}+n-1} \, \mathrm{d} t \int _{1}^{+ \infty } u^{{-1+\frac{c}{\lambda _{2}}-\lambda _{1}\varepsilon }} \,\mathrm{d} u. \end{aligned}

It follows that

\begin{aligned}& \frac{\Gamma ^{m+n}(1 / \rho )}{\rho ^{m+n-2} \Gamma (n / \rho )\Gamma (m / \rho )} \int _{1}^{+\infty } K(1, t) {t}^{- \frac{\beta +n+\lambda _{2}\varepsilon }{q}+n-1} \, \mathrm{d} t \int _{1}^{+ \infty } u^{{-1+\frac{c}{\lambda _{2}}-\lambda _{1}\varepsilon }} \,\mathrm{d} u \\& \quad \leq \frac{M}{\varepsilon \lambda ^{1/p}_{1}\lambda ^{1/q}_{2}} \biggl(\frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \biggr)^{1 / p} \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \biggr)^{1 / q}< + \infty . \end{aligned}

But since $$0<\varepsilon <\frac{c}{\lambda _{1}\lambda _{2}}$$, we have $$\frac{c}{\lambda _{2}}-\lambda _{1}\varepsilon >0$$ and $$\int _{1}^{+\infty } u^{-1+\frac{c}{\lambda _{2}}-\lambda _{1} \varepsilon } \,\mathrm{d} u=+\infty$$, which is contradictory, hence $$c > 0$$ is not valid.

If $$c<0$$, take $$0<\varepsilon <\frac{-c}{\lambda _{1}\lambda _{2}}$$ and

\begin{aligned}& f(x)= \textstyle\begin{cases} { \Vert x \Vert _{m,\rho }^{(-\alpha -m+\lambda _{1}\varepsilon ) / p},} & {0< \Vert x \Vert _{m,\rho } \leq 1}, \\ {0,} & { \Vert x \Vert _{m,\rho }>1}.\end{cases}\displaystyle \\& g(y)= \textstyle\begin{cases} { \Vert y \Vert _{n,\rho }^{(-\beta -n+\lambda _{2}\varepsilon ) / q},} & {0< \Vert y \Vert _{n,\rho } \leq 1}, \\ {0,} & { \Vert y \Vert _{n, \rho }>1}.\end{cases}\displaystyle \end{aligned}

Similarly, we can get

\begin{aligned}& \frac{\Gamma ^{m+n}(1 / \rho )}{\rho ^{m+n-2} \Gamma (n / \rho )\Gamma (m / \rho )} \int _{0}^{1} K(1, t) {t}^{- \frac{\beta +n-\lambda _{2}\varepsilon }{q}+n-1} \, \mathrm{d} t \int _{0}^{1} u^{{-1+\frac{c}{\lambda _{2}}+\lambda _{1}\varepsilon }} \,\mathrm{d} u \\& \quad \leq \frac{M}{\varepsilon \lambda ^{1/p}_{1}\lambda ^{1/q}_{2}} \biggl(\frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \biggr)^{1 / p} \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \biggr)^{1 / q}< + \infty . \end{aligned}

Since $$0<\varepsilon <\frac{-c}{\lambda _{1}\lambda _{2}}$$, we obtain $$\frac{c}{\lambda _{2}}+\lambda _{1}\varepsilon <0$$ and $$\int _{0}^{1} u^{-1+\frac{c}{\lambda _{2}}+\lambda _{1}\varepsilon } \,\mathrm{d} u=+\infty$$, this is still a contradiction, hence $$c< 0$$ cannot hold.

To sum up, when $$\lambda _{1}>0$$, $$\lambda _{2}>0$$, we have $$c=0$$, that is, $$\frac{n\lambda _{1}-\alpha \lambda _{2}}{p}+ \frac{m\lambda _{2}-\beta \lambda _{1}}{q}=0$$.

Moreover, consider the case of $$\lambda _{1}<0$$, $$\lambda _{2}<0$$. If $$c>0$$, take $$0<\varepsilon <\frac{c}{\lambda _{1}\lambda _{2}}$$ and

\begin{aligned}& f(x)= \textstyle\begin{cases} { \Vert x \Vert _{m,\rho }^{(-\alpha -m-\lambda _{1}\varepsilon ) / p},} & {0< \Vert x \Vert _{m,\rho } \leq 1}, \\ {0,} & { \Vert x \Vert _{m,\rho }>1},\end{cases}\displaystyle \\& g(y)= \textstyle\begin{cases} { \Vert y \Vert _{n,\rho }^{(-\beta -n-\lambda _{2}\varepsilon ) / q},} & {0< \Vert y \Vert _{n,\rho } \leq 1}, \\ {0,} & { \Vert y \Vert _{n, \rho }>1}.\end{cases}\displaystyle \end{aligned}

Then, by calculation,

\begin{aligned}& M \Vert f \Vert _{p, \alpha } \Vert g \Vert _{q, \beta } = \frac{M}{\varepsilon (-\lambda _{1})^{1/p}(-\lambda _{2})^{1/q}} \biggl(\frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \biggr)^{1 / p} \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \biggr)^{1 / q}, \\& { \int _{\mathbb{R}_{+}^{n}} \int _{\mathbb{R}_{+}^{m}} K\bigl( \Vert x \Vert _{m, \rho }, \Vert y \Vert _{n, \rho }\bigr) f(x)g(y) \,\mathrm{d} x \,\mathrm{d} y} \\& \quad = \int _{0< \Vert x \Vert _{m,\rho } \leq 1} \Vert x \Vert _{m,\rho }^{(-\alpha -m- \lambda _{1}\varepsilon ) / p} \biggl( \int _{0< \Vert y \Vert _{n,\rho } \leq 1} K\bigl( \Vert x \Vert _{m, \rho }, \Vert y \Vert _{n, \rho }\bigr) \Vert y \Vert _{n,\rho }^{(-\beta -n-\lambda _{2} \varepsilon ) / q} \,\mathrm{d} y \biggr) \,\mathrm{d} x \\& \quad = \int _{0< \Vert x \Vert _{m,\rho } \leq 1} \Vert x \Vert _{m,\rho }^{- \frac{\alpha +m+\lambda _{1}\varepsilon }{p}} \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \int _{0}^{1} K \bigl({ \Vert x \Vert _{m,\rho }}, u \bigr) {u}^{- \frac{\beta +n+\lambda _{2}\varepsilon }{q}+n-1} \,\mathrm{d} u \biggr) \, \mathrm{d} x \\& \quad = \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \int _{0< \Vert x \Vert _{m,\rho } \leq 1} \Vert x \Vert _{m,\rho }^{- \frac{\alpha +m+\lambda _{1}\varepsilon }{p}} \biggl( \int _{0}^{1} K \bigl({1, u \Vert x \Vert ^{-\lambda _{1}/\lambda _{2}}_{m,\rho }} \bigr) {u}^{- \frac{\beta +n+\lambda _{2}\varepsilon }{q}+n-1} \,\mathrm{d} u \biggr) \,\mathrm{d} x \\& \quad = \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \int _{0< \Vert x \Vert _{m,\rho } \leq 1} \Vert x \Vert _{m,\rho }^{- \frac{\alpha +m+\lambda _{1}\varepsilon }{p}+ \frac{\lambda _{1}}{\lambda _{2}} (- \frac{\beta +n+\lambda _{2}\varepsilon }{q}+n-1 )+ \frac{\lambda _{1}}{\lambda _{2}}} \\& \qquad {}\times \biggl( \int _{0}^{ \Vert x \Vert ^{-\lambda _{1}/\lambda _{2}}_{m,\rho }} K(1, t) {t}^{- \frac{\beta +n+\lambda _{2}\varepsilon }{q}+n-1} \, \mathrm{d} t \biggr) \,\mathrm{d} x \\& \quad = \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \int _{0< \Vert x \Vert _{m,\rho } \leq 1} \Vert x \Vert _{m,\rho }^{{-m+ \frac{c}{\lambda _{2}}-\lambda _{1}\varepsilon }} \biggl( \int _{0}^{ \Vert x \Vert ^{-\lambda _{1}/\lambda _{2}}_{m,\rho }} K(1, t) {t}^{- \frac{\beta +n+\lambda _{2}\varepsilon }{q}+n-1} \, \mathrm{d} t \biggr) \,\mathrm{d} x \\& \quad \geq \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \int _{0< \Vert x \Vert _{m,\rho } \leq 1} \Vert x \Vert _{m,\rho }^{{-m+ \frac{c}{\lambda _{2}}-\lambda _{1}\varepsilon }} \biggl( \int _{0}^{1} K(1, t) {t}^{- \frac{\beta +n+\lambda _{2}\varepsilon }{q}+n-1} \, \mathrm{d} t \biggr) \,\mathrm{d} x \\& \quad = \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \int _{0}^{1} K(1, t) {t}^{- \frac{\beta +n+\lambda _{2}\varepsilon }{q}+n-1} \, \mathrm{d} t \int _{0< \Vert x \Vert _{m,\rho } \leq 1} \Vert x \Vert _{m,\rho }^{{-m+\frac{c}{\lambda _{2}}- \lambda _{1}\varepsilon }} \,\mathrm{d} x \\& \quad = \frac{\Gamma ^{m+n}(1 / \rho )}{\rho ^{m+n-2} \Gamma (n / \rho )\Gamma (m / \rho )} \int _{0}^{1} K(1, t) {t}^{- \frac{\beta +n+\lambda _{2}\varepsilon }{q}+n-1} \, \mathrm{d} t \int _{0}^{1} u^{{-1+\frac{c}{\lambda _{2}}-\lambda _{1}\varepsilon }} \,\mathrm{d} u. \end{aligned}

It follows that

\begin{aligned}& \frac{\Gamma ^{m+n}(1 / \rho )}{\rho ^{m+n-2} \Gamma (n / \rho )\Gamma (m / \rho )} \int _{0}^{1} K(1, t) {t}^{- \frac{\beta +n+\lambda _{2}\varepsilon }{q}+n-1} \, \mathrm{d} t \int _{0}^{1} u^{{-1+\frac{c}{\lambda _{2}}-\lambda _{1}\varepsilon }} \,\mathrm{d} u \\& \quad \leq \frac{M}{\varepsilon (-\lambda _{1})^{1/p}(-\lambda _{2})^{1/q}} \biggl(\frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \biggr)^{1 / p} \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \biggr)^{1 / q}< + \infty . \end{aligned}

Since $$0<\varepsilon <\frac{c}{\lambda _{1}\lambda _{2}}$$ and $$\lambda _{1}<0$$, then $$\frac{c}{\lambda _{2}}-\lambda _{1}\varepsilon <0$$ and $$\int _{0}^{1} u^{-1+\frac{c}{\lambda _{2}}-\lambda _{1}\varepsilon } \,\mathrm{d} u=+\infty$$. This is a contradiction, therefore $$c > 0$$ cannot hold.

If $$c<0$$, take $$0<\varepsilon <\frac{-c}{\lambda _{1}\lambda _{2}}$$ and

\begin{aligned}& f(x)= \textstyle\begin{cases} { \Vert x \Vert _{m,\rho }^{(-\alpha -m+\lambda _{1}\varepsilon ) / p},} & { \Vert x \Vert _{m,\rho }\geq 1}, \\ {0,} & {0< \Vert x \Vert _{m,\rho }< 1}.\end{cases}\displaystyle \\& g(y)= \textstyle\begin{cases} { \Vert y \Vert _{n,\rho }^{(-\beta -n+\lambda _{2}\varepsilon ) / q},} & { \Vert y \Vert _{n, \rho } \geq 1}, \\ {0,} & {0< \Vert y \Vert _{n, \rho }< 1}.\end{cases}\displaystyle \end{aligned}

Similarly,

\begin{aligned}& \frac{\Gamma ^{m+n}(1 / \rho )}{\rho ^{m+n-2} \Gamma (n / \rho )\Gamma (m / \rho )} \int _{1}^{+\infty } K(1, t) {t}^{- \frac{\beta +n-\lambda _{2}\varepsilon }{q}+n-1} \, \mathrm{d} t \int _{1}^{+ \infty } u^{{-1+\frac{c}{\lambda _{2}}+\lambda _{1}\varepsilon }} \,\mathrm{d} u \\& \quad \leq \frac{M}{\varepsilon (-\lambda _{1})^{1/p}(-\lambda _{2})^{1/q}} \biggl(\frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \biggr)^{1 / p} \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \biggr)^{1 / q}< + \infty . \end{aligned}

Since $$0<\varepsilon <\frac{-c}{\lambda _{1}\lambda _{2}}$$ and $$\lambda _{1}<0$$, we have $$\frac{c}{\lambda _{2}}+\lambda _{1}\varepsilon >0$$ and $$\int _{1}^{+\infty } u^{-1+\frac{c}{\lambda _{2}}+\lambda _{1} \varepsilon } \,\mathrm{d} u=+\infty$$. That is still a contradiction, so $$c< 0$$ does not hold either.

To sum up, when $$\lambda _{1}<0$$, $$\lambda _{2}<0$$, we still have $$c=0$$, that is, $$\frac{n\lambda _{1}-\alpha \lambda _{2}}{p}+ \frac{m\lambda _{2}-\beta \lambda _{1}}{q}=0$$.

Conversely, if $$\frac{n\lambda _{1}-\alpha \lambda _{2}}{p}+ \frac{m\lambda _{2}-\beta \lambda _{1}}{q}=0$$, set $$a=\frac{\alpha +m}{p q}$$, $$b=\frac{\beta +n}{p q}$$, it follows from Hölder’s inequality and Lemma 1.2 that

\begin{aligned} & { \int _{\mathbb{R}_{+}^{n}} \int _{\mathbb{R}_{+}^{m}} K\bigl( \Vert x \Vert _{m, \rho }, \Vert y \Vert _{n, \rho }\bigr) f(x)g(y) \,\mathrm{d} x \,\mathrm{d} y} \\ &\quad = \int _{\mathbb{R}_{+}^{n}} \int _{\mathbb{R}_{+}^{m}} K\bigl( \Vert x \Vert _{m, \rho }, \Vert y \Vert _{n, \rho }\bigr) \biggl( \frac{ \Vert x \Vert _{m,\rho }^{a}}{ \Vert y \Vert _{n,\rho }^{b}} f(x) \biggr) \biggl( \frac{ \Vert y \Vert _{n,\rho }^{b}}{ \Vert x \Vert _{m,\rho }^{a}} g(y) \biggr) \,\mathrm{d} x \,\mathrm{d} y \\ &\quad \leq \biggl( \int _{\mathbb{R}_{+}^{n}} \int _{\mathbb{R}_{+}^{m}} K\bigl( \Vert x \Vert _{m, \rho }, \Vert y \Vert _{n, \rho }\bigr) \frac{ \Vert x \Vert _{m,\rho }^{a p}}{ \Vert y \Vert _{n,\rho }^{b p}} f^{p}(x) \,\mathrm{d} x \,\mathrm{d} y \biggr)^{1 / p} \\ &\qquad {} \times \biggl( \int _{\mathbb{R}_{+}^{n}} \int _{\mathbb{R}_{+}^{m}} K\bigl( \Vert x \Vert _{m, \rho }, \Vert y \Vert _{n, \rho }\bigr) \frac{ \Vert y \Vert _{n,\rho }^{b q}}{ \Vert x \Vert _{m,\rho }^{a q}} g^{q}(y) \,\mathrm{d} x \,\mathrm{d} y \biggr)^{1 / q} \\ &\quad = \biggl[ \int _{\mathbb{R}_{+}^{m}} \Vert x \Vert _{m,\rho }^{ \frac{\alpha +m}{q}} f^{p}(x) \biggl( \int _{\mathbb{R}_{+}^{n}} \Vert y \Vert _{n, \rho }^{-\frac{\beta +n}{q}} K\bigl( \Vert x \Vert _{m, \rho }, \Vert y \Vert _{n, \rho }\bigr) \,\mathrm{d} y \biggr)\,\mathrm{d} x \biggr]^{1 / p} \\ &\qquad {} \times \biggl[ \int _{\mathbb{R}_{+}^{n}} \Vert y \Vert _{n,\rho }^{ \frac{\beta +n}{p}} g^{q}(y) \biggl( \int _{\mathbb{R}_{+}^{m}} \Vert x \Vert _{m, \rho }^{-\frac{\alpha +m}{p}} K\bigl( \Vert x \Vert _{m, \rho }, \Vert y \Vert _{n, \rho }\bigr) \,\mathrm{d} x \biggr) \,\mathrm{d} y \biggr]^{1 / q} \\ &\quad = \biggl( \int _{\mathbb{R}_{+}^{m}} \Vert x \Vert _{m,\rho }^{ \frac{\alpha +m}{q}} f^{p}(x) \omega _{2}(n, \beta , q,x)\,\mathrm{d} x \biggr)^{1 / p} \biggl( \int _{\mathbb{R}_{+}^{n}} \Vert y \Vert _{n,\rho }^{ \frac{\beta +n}{p}} g^{q}(y) \omega _{1}(m,\alpha , p, y) \,\mathrm{d} y \biggr)^{1 / q} \\ &\quad = \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \biggr)^{1 / p} \biggl( \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \biggr)^{1 / q} \\ &\qquad {}\times W_{1}^{1 / q} W_{2}^{1 / p} \biggl( \int _{\mathbb{R}_{+}^{m}} \Vert x \Vert _{m,\rho }^{\frac{\alpha +m}{q}+\frac{\lambda _{1}}{\lambda _{2}} (-\frac{\beta +n}{q}+n )} f^{p}(x)\,\mathrm{d} x \biggr)^{1 / p} \\ &\qquad {} \times \biggl( \int _{\mathbb{R}_{+}^{n}} \Vert y \Vert _{n,\rho }^{ \frac{\beta +n}{p}+\frac{\lambda _{2}}{\lambda _{1}} (- \frac{\alpha +m}{p}+m )} g^{q}(y) \,\mathrm{d} y \biggr)^{1 / q} \\ &\quad = \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \biggr)^{1 / p} \biggl( \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \biggr)^{1 / q} W_{1}^{1 / q} W_{2}^{1 / p} \\ &\qquad {} \times \biggl( \int _{\mathbb{R}_{+}^{m}} \Vert x \Vert _{m,\rho }^{\alpha } f^{p}(x) \,\mathrm{d} x \biggr)^{1 / p} \biggl( \int _{\mathbb{R}_{+}^{n}} \Vert y \Vert _{n, \rho }^{\beta } g^{q}(y) \,\mathrm{d} y \biggr)^{1 / q} \\ &\quad = \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \biggr)^{1 / p} \biggl( \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \biggr)^{1 / q} W_{1}^{1 / q} W_{2}^{1 / p} \Vert f \Vert _{p, \alpha } \Vert g \Vert _{q, \beta }. \end{aligned}

Arbitrarily take a constant M satisfying

$$M \geq \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \biggr)^{1 / p} \biggl( \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \biggr)^{1 / q} W_{1}^{1 / q} W_{2}^{1 / p},$$

then

$$\int _{\mathbb{R}_{+}^{n}} \int _{\mathbb{R}_{+}^{m}} K\bigl( \Vert x \Vert _{m, \rho }, \Vert y \Vert _{n, \rho }\bigr) f(x)g(y) \,\mathrm{d} x \,\mathrm{d} y \leq M \Vert f \Vert _{p, \alpha } \Vert g \Vert _{q, \beta }.$$

Thus (5) holds.

(ii) Assume that there is a constant $$M_{0}$$ satisfying

\begin{aligned} M_{0}< \frac{W_{0}}{ \vert \lambda _{1} \vert ^{1/q} \vert \lambda _{2} \vert ^{1/p}} \biggl( \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \biggr)^{1 / q} \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \biggr)^{1 / p} \end{aligned}
(6)

such that, for any $$f(x) \in L_{p}^{\alpha }(\mathbb{R}_{+}^{m})$$, $$g(y) \in L_{q}^{\beta } (\mathbb{R}_{+}^{n} )$$, we have

$$\int _{\mathbb{R}_{+}^{n}} \int _{\mathbb{R}_{+}^{m}} K\bigl( \Vert x \Vert _{m, \rho }, \Vert y \Vert _{n, \rho }\bigr) f(x)g(y) \,\mathrm{d} x \,\mathrm{d} y \leq M_{0} \Vert f \Vert _{p, \alpha } \Vert g \Vert _{q, \beta }.$$

Take sufficiently small $$\varepsilon >0$$, $$\delta >0$$, and set

\begin{aligned}& f(x)= \textstyle\begin{cases} { \Vert x \Vert _{m,\rho }^{(-\alpha -m- \vert \lambda _{1} \vert \varepsilon ) / p},} & { \Vert x \Vert _{m,\rho }\geq \delta }, \\ {0,} & {0< \Vert x \Vert _{m,\rho }< \delta }.\end{cases}\displaystyle \\& g(y)= \textstyle\begin{cases} { \Vert y \Vert _{n,\rho }^{(-\beta -n- \vert \lambda _{2} \vert \varepsilon ) / q},} & { \Vert y \Vert _{n,\rho } \geq 1}, \\ {0,} & {0< \Vert y \Vert _{n, \rho }< 1}.\end{cases}\displaystyle \end{aligned}

It can be obtained by calculation that

\begin{aligned} M_{0} \Vert f \Vert _{p, \alpha } \Vert g \Vert _{q, \beta } =& M_{0} \biggl( \int _{ \Vert x \Vert _{m, \rho }\geq \delta } \Vert x \Vert _{m,\rho }^{-m- \vert \lambda _{1} \vert \varepsilon } \,\mathrm{d} x \biggr)^{1 / p} \biggl( \int _{ \Vert y \Vert _{m,\rho } \geq 1} \Vert y \Vert _{n,\rho }^{-n- \vert \lambda _{2} \vert \varepsilon } \,\mathrm{d} y \biggr)^{1 / q} \\ =& \frac{M_{0}\cdot \delta ^{-{ \vert \lambda _{1} \vert \varepsilon /p}}}{\varepsilon \vert \lambda _{1} \vert ^{1/p} \vert \lambda _{2} \vert ^{1/q}} \biggl(\frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \biggr)^{1 / p} \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \biggr)^{1 / q}. \end{aligned}

Since $$\frac{n\lambda _{1}-\alpha \lambda _{2}}{p}+ \frac{m\lambda _{2}-\beta \lambda _{1}}{q}=0$$,

\begin{aligned} & \int _{\mathbb{R}_{+}^{n}} \int _{\mathbb{R}_{+}^{m}} K\bigl( \Vert x \Vert _{m, \rho }, \Vert y \Vert _{n, \rho }\bigr) f(x)g(y) \,\mathrm{d} x \,\mathrm{d} y \\ &\quad = \int _{ \Vert y \Vert _{n,\rho } \geq 1} \Vert y \Vert _{n,\rho }^{(-\beta -n- \vert \lambda _{2} \vert \varepsilon ) / q} \biggl( \int _{ \Vert x \Vert _{m,\rho } \geq \delta } \Vert x \Vert _{m, \rho }^{(-\alpha -m- \vert \lambda _{1} \vert \varepsilon ) / p} K\bigl( \Vert x \Vert _{m, \rho }, \Vert y \Vert _{n, \rho }\bigr) \,\mathrm{d} x \biggr)\,\mathrm{d} y \\ &\quad = \int _{ \Vert y \Vert _{n,\rho } \geq 1} \Vert y \Vert _{n,\rho }^{(-\beta -n- \vert \lambda _{2} \vert \varepsilon ) / q} \biggl( \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \int _{ \delta }^{+\infty } u^{-\frac{\alpha +m+ \vert \lambda _{1} \vert \varepsilon }{p}+m-1} K\bigl(u, \Vert y \Vert _{n, \rho }\bigr) \,\mathrm{d} u \biggr)\,\mathrm{d} y \\ &\quad = \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \int _{ \Vert y \Vert _{n,\rho } \geq 1} \Vert y \Vert _{n,\rho }^{(-\beta -n- \vert \lambda _{2} \vert \varepsilon ) / q} \\ &\qquad {}\times \biggl( \int _{\delta }^{+\infty } u^{- \frac{\alpha +m+ \vert \lambda _{1} \vert \varepsilon }{p}+m-1} K\bigl(u \Vert y \Vert ^{- \lambda _{2}/\lambda _{1}}_{n, \rho }, 1\bigr) \,\mathrm{d} u \biggr) \,\mathrm{d} y \\ &\quad = \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \int _{ \Vert y \Vert _{n,\rho } \geq 1} \Vert y \Vert _{n,\rho }^{- \frac{\beta +n+ \vert \lambda _{2} \vert \varepsilon }{q}+ \frac{\lambda _{2}}{\lambda _{1}} (- \frac{\alpha +m+ \vert \lambda _{1} \vert \varepsilon }{p} +m-1 )+ \frac{\lambda _{2}}{\lambda _{1}}} \\ &\qquad {}\times \biggl( \int _{\delta \Vert y \Vert ^{-\lambda _{2}/\lambda _{1}}_{n, \rho }}^{+\infty } {t}^{- \frac{\alpha +m+ \vert \lambda _{1} \vert \varepsilon }{p}+m-1} K(t, 1) \, \mathrm{d} t \biggr) \,\mathrm{d} y \\ &\quad = \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \int _{ \Vert y \Vert _{n,\rho } \geq 1} \Vert y \Vert _{n,\rho }^{\frac{-1}{\lambda _{1}} (n\lambda _{1}+\frac{\lambda _{1} \vert \lambda _{2} \vert \varepsilon }{q}+ \frac{ \vert \lambda _{1} \vert \lambda _{2} \varepsilon }{p} )} \\ &\qquad {}\times \biggl( \int _{\delta \Vert y \Vert _{n,p}^{-\lambda _{2}/\lambda _{1}}}^{+\infty } t^{- \frac{\alpha +m+ \vert \lambda _{1} \vert \varepsilon }{p}+m-1} K(t, 1) \, \mathrm{d} t \biggr)\,\mathrm{d} y \\ &\quad \geq \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \int _{ \Vert y \Vert _{n,\rho } \geq 1} \Vert y \Vert _{n,\rho }^{-n- \vert \lambda _{2} \vert \varepsilon } \biggl( \int _{\delta }^{+\infty } t^{- \frac{\alpha +m+ \vert \lambda _{1} \vert \varepsilon }{p}+m-1} K(t, 1) \, \mathrm{d} t \biggr)\,\mathrm{d} y \\ &\quad = \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \int _{\delta }^{+\infty } t^{- \frac{\alpha +m+ \vert \lambda _{1} \vert \varepsilon }{p}+m-1} K(t, 1) \, \mathrm{d} t \int _{ \Vert y \Vert _{n,\rho } \geq 1} \Vert y \Vert _{n,\rho }^{-n- \vert \lambda _{2} \vert \varepsilon } \,\mathrm{d} y \\ &\quad = \frac{\Gamma ^{m+n}(1 / \rho )}{\rho ^{m+n-2} \Gamma (n / \rho )\Gamma (m / \rho )} \int _{\delta }^{+\infty } t^{- \frac{\alpha +m+ \vert \lambda _{1} \vert \varepsilon }{p}+m-1} K(t, 1) \, \mathrm{d} t \int _{1}^{+\infty } u^{-1- \vert \lambda _{2} \vert \varepsilon } \,\mathrm{d} u \\ &\quad = \frac{\Gamma ^{m+n}(1 / \rho )}{\varepsilon \vert \lambda _{2} \vert \rho ^{m+n-2} \Gamma (n / \rho )\Gamma (m / \rho )} \int _{\delta }^{+\infty } t^{- \frac{\alpha +m+ \vert \lambda _{1} \vert \varepsilon }{p}+m-1} K(t, 1) \, \mathrm{d} t. \end{aligned}

Consequently,

\begin{aligned} & \frac{\Gamma ^{m+n}(1 / \rho )}{ \vert \lambda _{2} \vert \rho ^{m+n-2} \Gamma (n / \rho )\Gamma (m / \rho )} \int _{\delta }^{+\infty } t^{- \frac{\alpha +m+ \vert \lambda _{1} \vert \varepsilon }{p}+m-1} K(t, 1) \, \mathrm{d} t \\ &\quad \leq \frac{M_{0} \delta ^{- \vert \lambda _{1} \vert \varepsilon /p }}{ \vert \lambda _{1} \vert ^{1/p} \vert \lambda _{2} \vert ^{1/q}} \biggl(\frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \biggr)^{1 / p} \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \biggr)^{1 / q}. \end{aligned}

Let $$\varepsilon \rightarrow 0^{+}$$, and by using the famous Fatou lemma, we obtain

\begin{aligned} & \frac{\Gamma ^{m+n}(1 / \rho )}{ \vert \lambda _{2} \vert \rho ^{m+n-2} \Gamma (n / \rho )\Gamma (m / \rho )} \int _{\delta }^{+\infty } t^{-\frac{\alpha +m}{p}+m-1} K(t, 1) \, \mathrm{d} t \\ &\quad \leq \frac{M_{0}}{ \vert \lambda _{1} \vert ^{1/p} \vert \lambda _{2} \vert ^{1/q}} \biggl( \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \biggr)^{1 / p} \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \biggr)^{1 / q}. \end{aligned}

Let again $$\delta \rightarrow 0^{+}$$, then

$$\frac{\Gamma ^{m+n}(1 / \rho )W_{1}}{ \vert \lambda _{2} \vert \rho ^{m+n-2} \Gamma (n / \rho )\Gamma (m / \rho )} \leq \frac{M_{0}}{ \vert \lambda _{1} \vert ^{1/p} \vert \lambda _{2} \vert ^{1/q}} \biggl( \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \biggr)^{1 / p} \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \biggr)^{1 / q}.$$

It follows that

$$\frac{W_{0}}{ \vert \lambda _{1} \vert ^{1/q} \vert \lambda _{2} \vert ^{1/p}} \biggl( \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \biggr)^{1 / q} \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \biggr)^{1 / p}\leq M_{0}.$$

$$\frac{W_{0}}{ \vert \lambda _{1} \vert ^{1/q} \vert \lambda _{2} \vert ^{1/p}} \biggl( \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \biggr)^{1 / q} \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \biggr)^{1 / p}$$

is the best constant factor of (5). □

## 3 Applications in operator theory

Let $$p>1$$, $$\rho >0$$, $$m,n\in \mathbb{N}$$, $$\alpha ,\beta \in \mathbb{R}$$, $$K(u,v)$$ be nonnegative measurable. Define

$$T(f) (y)= \int _{\mathbb{R}_{+}^{m}} K\bigl( \Vert x \Vert _{m, \rho }, \Vert y \Vert _{n, \rho }\bigr) f(x) \,\mathrm{d} x,\quad f(x) \in L_{p}^{\alpha }\bigl(\mathbb{R}_{+}^{m} \bigr).$$
(7)

Then T is a singular integral operator defined on $$L_{p}^{\alpha }(\mathbb{R}_{+}^{m})$$. Using this operator and according to Hilbert type integral operator theory, (5) is equivalent to

$$\bigl\Vert T(f) \bigr\Vert _{p,\beta (1-p)}\leq M \Vert f \Vert _{p, \alpha },$$

so we get the following.

### Theorem 3.1

Under the same conditions as in Theorem 2.1, let the singular integral operator T be defined as in (7). Then

(i) T is a bounded operator from $$L_{p}^{\alpha }(\mathbb{R}_{+}^{m})$$ to $$L_{p}^{\beta (1-p)} (\mathbb{R}_{+}^{n} )$$ if and only if $$\frac{n\lambda _{1}-\alpha \lambda _{2}}{p}+ \frac{m\lambda _{2}-\beta \lambda _{1}}{q}=0$$.

(ii) When T is a bounded operator from $$L_{p}^{\alpha }(\mathbb{R}_{+}^{m})$$ to $$L_{p}^{\beta (1-p)} (\mathbb{R}_{+}^{n} )$$, the operator norm of T is

$$\Vert T \Vert = \frac{W_{0}}{ \vert \lambda _{1} \vert ^{1/q} \vert \lambda _{2} \vert ^{1/p}} \biggl( \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \biggr)^{1 / q} \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \biggr)^{1 / p}.$$

### Corollary 3.1

Let $$\frac{1}{p}+\frac{1}{q}=1(p>1)$$, $$\rho >0$$, $$\lambda >0$$, $$\lambda _{1} \lambda _{2}>0$$, $$m,n\in \mathbb{N}$$, $$\alpha ,\beta \in \mathbb{R}$$, $$0< \frac{1}{\rho \lambda _{1}} ( \frac{m}{q}-\frac{\alpha }{p} )<\lambda$$. Define a singular integral operator T by

$$T(f) (y)= \int _{\mathbb{R}_{+}^{m}} \frac{f(x)}{ [1+(\sum_{k=1}^{m} x_{k}^{\rho })^{\lambda _{1}}/(\sum_{k=1}^{n} y_{k}^{\rho })^{\lambda _{2}} ]^{\lambda }} \,\mathrm{d} x.$$

Then $$T: L_{p}^{\alpha }(\mathbb{R}_{+}^{m}) \rightarrow L_{p}^{\beta (1-p)} (\mathbb{R}_{+}^{n} )$$ is a bounded operator if and only if $$\frac{n\lambda _{1}-\alpha \lambda _{2}}{p}+ \frac{m\lambda _{2}-\beta \lambda _{1}}{q}=0$$. And when T is bounded, its operator norm is

\begin{aligned} \Vert T \Vert =& \frac{1}{ \vert \lambda _{1} \vert ^{1/q} \vert \lambda _{2} \vert ^{1/p}} B \biggl( \frac{1}{\rho \lambda _{1}} \biggl( \frac{m}{q}-\frac{\alpha }{p} \biggr), \lambda - \frac{1}{\rho \lambda _{1}} \biggl( \frac{m}{q}- \frac{\alpha }{p} \biggr) \biggr) \\ &{}\times \biggl( \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m} \Gamma (m / \rho )} \biggr)^{1 / q} \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n} \Gamma (n / \rho )} \biggr)^{1 / p}, \end{aligned}

where $$B(u,v)$$ represents the beta function.

### Proof

First, notice that

\begin{aligned} \frac{1}{ [1+(\sum_{k=1}^{m} x_{k}^{\rho })^{\lambda _{1}}/(\sum_{k=1}^{n} y_{k}^{\rho })^{\lambda _{2}} ]^{\lambda }} &= \frac{1}{ (1+ \Vert x \Vert _{m, \rho }^{\rho \lambda _{1}}/ \Vert y \Vert _{n, \rho }^{\rho \lambda _{2}} )^{\lambda }} \\ &=G\bigl( \Vert x \Vert ^{\rho \lambda _{1}}_{m, \rho }/ \Vert y \Vert ^{\rho \lambda _{2}}_{n, \rho }\bigr) =K\bigl( \Vert x \Vert _{m, \rho }, \Vert y \Vert _{n, \rho }\bigr) \end{aligned}

and

$$\frac{n\lambda _{1}-\alpha \lambda _{2}}{p}+ \frac{m\lambda _{2}-\beta \lambda _{1}}{q}=0$$

is equivalent to

$$\frac{n(\rho \lambda _{1})-\alpha (\rho \lambda _{2})}{p}+ \frac{m(\rho \lambda _{2})-\beta (\rho \lambda _{1})}{q}=0.$$

Since

\begin{aligned} W_{0} =& \vert \rho \lambda _{1} \vert W_{1} = \vert \rho \lambda _{1} \vert \int _{0}^{+ \infty } K(t, 1) t^{-\frac{\alpha +m}{p}+m-1} \, \mathrm{d} t \\ =& \vert \rho \lambda _{1} \vert \int _{0}^{+\infty } \frac{1}{ (1+t^{\rho \lambda _{1}} )^{\lambda }} t^{- \frac{\alpha +m}{p}+m-1} \,\mathrm{d} t = \int _{0}^{+\infty } \frac{1}{(1+u)^{\lambda }} u^{ \frac{1}{\rho \lambda _{1}} (\frac{m}{q}-\frac{\alpha }{p} )-1} \,\mathrm{d} u \\ =& B \biggl(\frac{1}{\rho \lambda _{1}} \biggl( \frac{m}{q}- \frac{\alpha }{p} \biggr), \lambda -\frac{1}{\rho \lambda _{1}} \biggl( \frac{m}{q}-\frac{\alpha }{p} \biggr) \biggr), \end{aligned}

we have

\begin{aligned}& \frac{W_{0}}{ \vert \rho \lambda _{1} \vert ^{1/q} \vert \rho \lambda _{2} \vert ^{1/p}} \biggl(\frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \biggr)^{1 / q} \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \biggr)^{1 / p} \\& \quad = \frac{1}{\rho \vert \lambda _{1} \vert ^{1/q} \vert \lambda _{2} \vert ^{1/p}} B \biggl( \frac{1}{\rho \lambda _{1}} \biggl( \frac{m}{q}-\frac{\alpha }{p} \biggr), \lambda - \frac{1}{\rho \lambda _{1}} \biggl( \frac{m}{q}- \frac{\alpha }{p} \biggr) \biggr) \\& \qquad {}\times \biggl( \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \biggr)^{1 / q} \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \biggr)^{1 / p} \\& \quad = \frac{1}{ \vert \lambda _{1} \vert ^{1/q} \vert \lambda _{2} \vert ^{1/p}} B \biggl( \frac{1}{\rho \lambda _{1}} \biggl( \frac{m}{q}-\frac{\alpha }{p} \biggr), \lambda - \frac{1}{\rho \lambda _{1}} \biggl( \frac{m}{q}- \frac{\alpha }{p} \biggr) \biggr) \\& \qquad {}\times \biggl( \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m} \Gamma (m / \rho )} \biggr)^{1 / q} \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n} \Gamma (n / \rho )} \biggr)^{1 / p}. \end{aligned}

According to Theorem 3.1, Corollary 3.1 holds. □

### Corollary 3.2

Let $$\frac{1}{p}+\frac{1}{q}=1(p>1)$$, $$\rho >0$$, $$\lambda _{1}>0$$, $$\lambda _{2}>0$$, $$m,n\in \mathbb{N}$$, $$\alpha ,\beta \in \mathbb{R}$$, $$-\lambda _{1}< \frac{m}{q}-\frac{\alpha }{p} <\lambda _{1}$$. Define a singular integral operator T by

$$T(f) (y)= \int _{\mathbb{R}_{+}^{m}} \frac{\min \{1, \Vert x \Vert ^{\lambda _{1}}_{m, \rho }/ \Vert y \Vert ^{\lambda _{2}}_{n, \rho }\}}{\max \{1, \Vert x \Vert ^{\lambda _{1}}_{m, \rho }/ \Vert y \Vert ^{\lambda _{2}}_{n, \rho }\}} f(x) \,\mathrm{d} x, \quad f(x) \in L_{p}^{\alpha }\bigl(\mathbb{R}_{+}^{m} \bigr).$$

Then $$T: L_{p}^{\alpha }(\mathbb{R}_{+}^{m}) \rightarrow L_{p}^{\beta (1-p)} (\mathbb{R}_{+}^{n} )$$ is a bounded operator if and only if $$\frac{n\lambda _{1}-\alpha \lambda _{2}}{p}+ \frac{m\lambda _{2}-\beta \lambda _{1}}{q}=0$$, and when T is bounded, its operator norm is

$$\Vert T \Vert = \frac{2\lambda ^{2}_{1}}{\lambda _{1}^{1/q} \lambda _{2}^{1/p} (\lambda _{1}+\frac{m}{q}-\frac{\alpha }{p} ) (\lambda _{1}-\frac{m}{q}+\frac{\alpha }{p} )} \biggl(\frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \biggr)^{1 / q} \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \biggr)^{1 / p}.$$

### Proof

Since $$-\lambda _{1}< \frac{m}{q}-\frac{\alpha }{p} <\lambda _{1}$$, then $$\frac{m}{q}-\frac{\alpha }{p} +\lambda _{1}>0$$ and $$\frac{m}{q}-\frac{\alpha }{p} -\lambda _{1}<0$$, therefore

\begin{aligned} W_{0} =&\lambda _{1} \int _{0}^{+\infty } K(t, 1) t^{- \frac{\alpha +m}{p}+m-1} \, \mathrm{d} t \\ =& \lambda _{1} \int _{0}^{+\infty } \frac{\min \{1,t^{\lambda _{1}}\}}{\max \{1,t^{\lambda _{1}}\}} t^{ \frac{m}{q}-\frac{\alpha }{p}-1} \,\mathrm{d} t\\ =& \lambda _{1} \int _{0}^{1} t^{\frac{m}{q}-\frac{\alpha }{p}+\lambda _{1}-1} \,\mathrm{d} t + \lambda _{1} \int _{1}^{+\infty } t^{\frac{m}{q}-\frac{\alpha }{p}- \lambda _{1}-1} \,\mathrm{d} t \\ =& \frac{\lambda _{1}}{\frac{m}{q}-\frac{\alpha }{p}+\lambda _{1}} - \frac{\lambda _{1}}{\frac{m}{q}-\frac{\alpha }{p}-\lambda _{1}} = \frac{-2\lambda ^{2}_{1}}{ (\frac{m}{q}-\frac{\alpha }{p}+\lambda _{1} ) (\frac{m}{q}-\frac{\alpha }{p}-\lambda _{1} )}. \end{aligned}

It follows that

\begin{aligned}& \frac{W_{0}}{ \vert \lambda _{1} \vert ^{1/q} \vert \lambda _{2} \vert ^{1/p}} \biggl( \frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \biggr)^{1 / q} \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \biggr)^{1 / p} \\& \quad = \frac{2\lambda ^{2}_{1}}{\lambda _{1}^{1/q} \lambda _{2}^{1/p} (\lambda _{1}+\frac{m}{q}-\frac{\alpha }{p} ) (\lambda _{1}-\frac{m}{q}+\frac{\alpha }{p} )} \biggl(\frac{\Gamma ^{m}(1 / \rho )}{\rho ^{m-1} \Gamma (m / \rho )} \biggr)^{1 / q} \biggl( \frac{\Gamma ^{n}(1 / \rho )}{\rho ^{n-1} \Gamma (n / \rho )} \biggr)^{1 / p}. \end{aligned}

According to Theorem 3.1, Corollary 3.2 holds. □

## Availability of data and materials

The data and material in this paper are effective.

## References

1. Hong, Y., Huang, Q., Yang, B.: The necessary and sufficient conditions for the existence of a kind of Hilbert-type multiple integral inequality with the non-homogeneous kernel and its applications. J. Inequal. Appl. 2017, 316 (2017)

2. Hong, Y., He, B., Yang, B.: Necessary and sufficient conditions for the validity of Hilbert type integral inequalities with a class of quasi-homogeneous kernels and its application in operator theory. J. Math. Inequal. 12(3), 777–788 (2018)

3. Rassias, M.Th., Yang, B., Raigorodskii, A.: On a half-discrete Hilbert-type inequality in the whole plane with the kernel of hyperbolic secant function related to the Hurwitz zeta function. In: Trigonometric Sums and Their Applications, pp. 229–259. Springer, Berlin (2020)

4. Rassias, M.Th., Yang, B.: On an equivalent property of a reverse Hilbert-type integral inequality related to the extended Hurwitz-zeta function. J. Math. Inequal. 13(2), 315–334 (2019)

5. Rassias, M.Th., Yang, B.: On a Hilbert-type integral inequality in the whole plane related to the extended Riemann zeta function. Complex Anal. Oper. Theory 13(4), 1765–1782 (2019)

6. Rassias, M.Th., Yang, B.: On a Hilbert-type integral inequality related to the extended Hurwitz zeta function in the whole plane. Acta Appl. Math. 160(1), 67–80 (2019)

7. Rassias, M.Th., Yang, B.: Equivalent properties of a Hilbert-type integral inequality with the best constant factor related to the Hurwitz zeta function. Ann. Funct. Anal. 9(2), 282–295 (2018)

8. Rassias, M.Th., Yang, B.: A half-discrete Hilbert-type inequality in the whole plane related to the Riemann zeta function. Appl. Anal. 97(9), 1505–1525 (2018)

9. Rassias, M.Th., Yang, B.: A Hilbert-type integral inequality in the whole plane related to the hypergeometric function and the beta function. J. Math. Anal. Appl. 428(2), 1286–1308 (2015)

10. Rassias, M.Th., Yang, B.: On a multidimensional Hilbert-type integral inequality associated to the gamma function. Appl. Math. Comput. 249, 408–418 (2014)

11. Rassias, M.Th., Yang, B.: A multidimensional half-discrete Hilbert-type inequality and the Riemann zeta function. Appl. Math. Comput. 225, 263–277 (2013)

12. Rassias, M.Th., Yang, B.: A multidimensional Hilbert-type integral inequality related to the Riemann zeta function. In: Applications of Mathematics and Informatics in Science and Engineering, pp. 417–433. Springer, New York (2014)

13. Yang, B., Liao, J.: Parameterized Multidimensional Hilbert-Type Inequalities. Scientific Research Publishing, USA (2020)

14. Yang, B.: On a more accurate multidimensional Hilbert-type inequality with parameters. Math. Inequal. Appl. 18(2), 429–441 (2015)

15. Cao, J., He, B., Hong, Y., Yang, B.: Equivalent conditions and applications of a class of Hilbert-type integral inequalities involving multiple functions with quasi-homogeneous kernels. J. Inequal. Appl. 2018, 206 (2018)

16. Yong, H.: A multidimensional generalization of Hardy-Hilbert’s integral inequality. Taiwan. J. Math. 12(2), 179–188 (2008)

17. He, B., Wang, Q.: A multiple Hilbert-type discrete inequality with a new kernel and best possible constant factor. J. Math. Anal. Appl. 431(2), 889–902 (2015)

18. Krnić, M., Vuković, P.: A class of Hilbert-type inequalities obtained via the improved Young inequality. Results Math. 71, 185–196 (2017)

19. Brevig, O.F.: Sharp norm estimates for composition operators and Hilbert-type inequalities. Bull. Lond. Math. Soc. 49(6), 965–978 (2017)

20. Tserendorj, B., Vandanjav, A., Azar, L.E.: A new discrete Hilbert-type inequality involving partial sums. J. Inequal. Appl. 2019 (2019) 127

21. Fichtingoloz, G.M.: A Course in Differential and Integral Calculus. People’s Education Press, Beijing (1957) (in Chinese)

## Acknowledgements

The authors thank the referee for his useful suggestions to reform the paper.

## Funding

This work is supported by the Innovation Team Construction Project of Guangdong Province (2018KCXTD020).

## Author information

Authors

### Contributions

BH carried out the mathematical studies, participated in the sequence alignment, and drafted the manuscript. ZL and YH participated in the design of the study and performed the numerical analysis. All authors read and approved the final manuscript.

### Corresponding author

Correspondence to Zhen Li.

## Ethics declarations

### Competing interests

The authors declare that they have no competing interests.

## Rights and permissions 